Sensory Quality Analysis of Herbal Beverages with Sweetener Proportions - Ralita Alma; Lilis Sulandari; Ila Huda Puspita Dewi; Mafisa Restami (Takaza Innovatix Labs Ltd., 2026)
Consumer acceptance of herbal drinks remains a challenge due to their bitter taste and strong spice aroma. This study aims to analyze the effect of the proportion of palm sugar and granulated sugar on the sensory quality of herbal drinks made from rhizomes and to determine the best formulation based on the results of sensory tests and nutritional content analysis. The study used a quantitative approach with an experimental method. The study population was herbal drink formulations with varying sweetener proportions, while the sample consisted of three treatments, namely the proportion of palm sugar and granulated sugar of 300:200, 400:100, and 500:0. Data collection used a sensory test sheet on a scale of 1 to 5 assessed by 35 panelists. Data were analyzed using One-Way ANOVA and Duncan's advanced test at a significance level of 5 percent, while nutritional content was analyzed using the Weibull, Kjeldahl, Luff-Schoorl, and Atwater System methods. The results showed that the proportion of sweetener had a significant effect on color attributes (p < 0.05), but did not significantly affect aroma, taste, aftertaste, and overall preference. The best formulation contained 0.42% fat, 0.86% protein, 9.18% carbohydrate, 8.90% total sugar, and 43.96 kcal energy per 100 mL. It was concluded that the proportion of 400 g palm sugar and 100 g granulated sugar produced the most balanced sensory quality, was efficient for production, and had the potential to be developed as a functional herbal drink that was more acceptable to consumers.